2011
DOI: 10.11564/25-2-248
|View full text |Cite
|
Sign up to set email alerts
|

The vulnerability of older adults:what do census data say?An application to Uganda

Abstract: Older adults are generally considered as being among the most vulnerable groups of the population. Yet, being over 55, 60 or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Our results generally fit within the literature on this topic. Research elsewhere has also found that older women are relatively vulnerable when they are not living with others, especially offspring (Cliggett 2005; Golaz and Rutaremwa 2011; Hoddinott 1992), and that caring for grandchildren may be a physical and mental burden for older women (Hadley et al 2011; Kamya and Poindexter 2009; Nyambedha, Wandibba and Aagaard-Hansen 2003). For these women, the association between health and co-residence with offspring could be partly related to stress, where research found that women in Kenya experienced lower levels of perceived stress when a greater number of adults were present in the household (Ice et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results generally fit within the literature on this topic. Research elsewhere has also found that older women are relatively vulnerable when they are not living with others, especially offspring (Cliggett 2005; Golaz and Rutaremwa 2011; Hoddinott 1992), and that caring for grandchildren may be a physical and mental burden for older women (Hadley et al 2011; Kamya and Poindexter 2009; Nyambedha, Wandibba and Aagaard-Hansen 2003). For these women, the association between health and co-residence with offspring could be partly related to stress, where research found that women in Kenya experienced lower levels of perceived stress when a greater number of adults were present in the household (Ice et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We conducted linear regression analysis separately by sex, because important differences for women and men in health-related outcomes associated with living arrangements have been consistently found in research elsewhere (Hughes and Waite 2002; Rahman 2001), including in other sub-Saharan settings (Golaz and Rutaremwa 2011). We ran regression analysis in two stages.…”
Section: Methodsmentioning
confidence: 99%
“…The modest sums paid out (about US $8 per month) are very far from enabling older adults to meet all of their needs. However, they represent a significant form of aid in rural areas, where 94 per cent of older people lived in 2002 (Golaz and Rutaremwa 2011), many of them on subsistence farming and with little if any monetary income (Oxford Policy Management 2013).…”
Section: Vulnerability and Resilience In The Ugandan Contextmentioning
confidence: 99%
“…National data have been analysed to give a broader picture of the situation of older people in Uganda. Different vulnerability indicators were tested on the 1991 and 2002 population census data (Antoine and Golaz 2011; Golaz and Rutaremwa 2011). Disabilities and ill health among older people were obtained using Uganda National Household Survey (UNHS) data (Wandera et al 2014, 2015).…”
Section: Vulnerability and Resilience In The Ugandan Contextmentioning
confidence: 99%
“…As a phenomenon, the ageing of the world population caught nations at different stages of their development and occurs at varying rates (see Tables 1 and 2). While population ageing in the developed countries was gradual and occurred when they had more or less resolved issues having to do with infrastructure, maternal and infant mortality, and population ageing in most developing countries is occurring when vital development issues are still unresolved as evidence in Uganda and Ghana (Golaz andRutaremwa, 2011, Tawiah, 2011) when financial resources are dwindling, and when institutional structures to address these issues are either nonexistent or very weak. Furthermore, the experiences which accompany the process are greatly influenced to a large extent by the prevailing sociocultural context in which the ageing is taking place.…”
Section: Introductionmentioning
confidence: 99%